2016
DOI: 10.1002/elan.201600265
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Concentration Distributions and Hydrogen Evolution on Corroding Magnesium Exposed to Aqueous Environments Using Scanning Electrochemical Microscopy

Abstract: 1IntroductionMagnesium and its alloys have ag reat potential for several industriala nd biomedical applications due to their non-toxicity and high strength-weight ratio, though their practical use is severely limited by their poor corrosion resistance in most aqueouse nvironments [1][2][3][4].I no rder to slow down this degradation, it is mandatory to gather precise knowledge about the mechanism of the process. Unfortunately,t he mechanism of magnesium corrosion remains controversial, and it presents certain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In this work, the SG/TC mode was employed to study the evolution of hydrogen gas (H 2 ) from a corroding surface when exposed to 5 mmol L −1 NaCl solution. H 2 evolution from the surfaces of different metals has been investigated by SECM in the SG/TC mode which allows their localized corrosion processes to be studied [ 38 , 39 , 40 , 41 ]. These previous studies reported the selective detection of reacting species released from the corrosion reactions when the materials are left unpolarized in the environment.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, the SG/TC mode was employed to study the evolution of hydrogen gas (H 2 ) from a corroding surface when exposed to 5 mmol L −1 NaCl solution. H 2 evolution from the surfaces of different metals has been investigated by SECM in the SG/TC mode which allows their localized corrosion processes to be studied [ 38 , 39 , 40 , 41 ]. These previous studies reported the selective detection of reacting species released from the corrosion reactions when the materials are left unpolarized in the environment.…”
Section: Methodsmentioning
confidence: 99%
“…(reaction 1). H22H++2e The local flux of H 2 gas from the surfaces of metal alloys has been investigated by SECM in the SG/TC mode …”
Section: Methodsmentioning
confidence: 99%
“…Thus, H 2 generation can be sensed in an oxidation reaction at the UME probe potential of 0.0 V versus Ag/AgCl. Several researchers studied the flux of H 2 gas evolving from the surface of magnesium based materials 10,14,[16][17][18][19] .…”
Section: Mg H O Mgmentioning
confidence: 99%